Friction stir extrusion of ultra-thin wall biodegradable magnesium alloy tubes — Microstructure and corrosion response. (March 2021) - Shunmugasamy, Vasanth C.; Khalid, Eisha; Mansoor, Bilal
Highlights: Ultra-thin biodegradable magnesium alloy tubes were fabricated using novel friction stir extrusion process. The inner edge of tube wall had refined grains and basal texture perpendicular to the extrusion direction. The corrosion response of the tube was influenced by grain size, texture evolution and residual stress. The corrosion started from the outer layer moving inward owing to microgalvanic coupling between inner and outer layers. Low temperature heat treatment of the tube resulted in lower corrosion rate and more uniform corrosion. Abstract: Magnesium alloys are increasingly being considered for structural systems across different industrial sectors, including precision components of biomedical devices owing to their high specific strength and stiffness, biodegradability. For example, tubular devices such as coronary stents manufacture require defect-free, high-quality tubes with thin walls (100 μm – 1 mm) as a precursor. Here, we have produced fully consolidated, structurally sound ultra-thin walled (∼ 400 μm) AZ31 Mg alloy tubes by friction stir back extrusion (FSE) — a relatively new severe deformation process used typically to manufacture thick metallic tubes and rods. The tube cross-sectional microstructure was layered and consisted of a severely deformed stir zone with refined grains near the inner edge, a back-extruded zone with small grains near the outer edge, and a thermomechanically affected zone (TMAZ) with coarse grains develop within the central region. On the other hand, the inner tube surface microstructure had an average grain size of 4.1 ± 1.9 μm and a strong basal texture. In comparison, the outer tube surface microstructure was coarse, with an average grain size of 13.3 ± 6.4 μm with no preferred orientation. The microhardness variation along the tube wall thickness indicated the operation of multiple deformation paths during FSE. Upon exposure to Hank's balanced salt solution at 37 °C, microgalvanic coupling resulting from the gradient through-the-thickness grain size and texture differences between the tube inner and outer surfaces, and residual strain arising from the FSE process, promoted a localized attack that preferentially initiated on the outer tube surface and progressed inwards. Static recovery induced by a short duration heat treatment at low temperature did not alter the microstructure but promoted a more general corrosion attack with a significantly reduced corrosion rate. Our results establish that FSE is a viable single-step process to manufacture ultra-thin Mg alloy tubes suitable for degradable precision tubular applications.